2013
DOI: 10.1108/13673271311315213
|View full text |Cite
|
Sign up to set email alerts
|

Forming mechanisms and structures of a knowledge transfer network: theoretical and simulation research

Abstract: PurposeThis paper aims to analyze the exchange and reciprocal mechanism behind individual knowledge transfer activities as well as their impact on the individual knowledge transfer networks.Design/methodology/approachThe author conducted theoretical and simulation research. Agent‐based technology is employed to construct an agent dynamics agent‐based model that simulates and explains how an individual initiates the evolution of a knowledge network through knowledge transfer activities.FindingsThe results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
(28 reference statements)
0
33
0
1
Order By: Relevance
“…Compared with the classical game theory, the simulation method pays more attention to the dynamic process of knowledge sharing. For example, Wang [42] constructs an agent dynamics agent-based model to analyze the exchange and reciprocal mechanism behind individual knowledge transfer activities as well as their impact on the individual knowledge transfer networks. The results demonstrate that the exchange mechanism can improve the knowledge levels of the network members.…”
Section: Knowledge Sharing Behavior Among Enterprisesmentioning
confidence: 99%
“…Compared with the classical game theory, the simulation method pays more attention to the dynamic process of knowledge sharing. For example, Wang [42] constructs an agent dynamics agent-based model to analyze the exchange and reciprocal mechanism behind individual knowledge transfer activities as well as their impact on the individual knowledge transfer networks. The results demonstrate that the exchange mechanism can improve the knowledge levels of the network members.…”
Section: Knowledge Sharing Behavior Among Enterprisesmentioning
confidence: 99%
“…Hocking et al (2007) investigated how expatriate contributes in transnational strategy company reach the purpose of global efficiency, learning process, and national and local reponse. Interesting results by Wang (2013) showed that both mechanisms will be able to improve the knowledge rate of network members. Changeable mechanism will be much more efficient, since it can improve both sides' value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Changeable mechanism will be much more efficient, since it can improve both sides' value. According to information speed based on economy development, knowledge has become strategic asset in an organization (Bollinger and Smith in Wang, 2013). The study on knowledge transfer comes from the discussion on technology transfer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social exchanges are long-term relationships involving trust, loyalty and mutual commitments that evolve over time (Cropanzano & Mitchell, 2005), i.e., they evolve in a way that generates obligations on both parts (Emerson, 1976). Exchange efficiency can be achieved through knowledge sharing (Wang, 2013), which is a kind of exchange behaviour (Cyr & Choo, 2010;Huang, Davison, & Gu, 2008;Lin, 2014).…”
Section: Introductionmentioning
confidence: 99%